ما لم يسم فاعله في العربية: جمعا ودراسة - المقوشي، عمر بن علي (جامعة المنيا - كلية دار العلوم, 2022)
هذا بحث في اللغة يتناول ظاهرة البناء للمجهول في اللغة العربية؛ وقد جعل في مقدمة، ومبحثين، وخاتمة، أما المبحث الأول فتناول مسائل عامة للمبني للمجهول، أحدها ما للفعل من أهمية في اللغة، فمنه تشتق الأفعال والأسماء حتى تتسع اللغة للتعبير عن المعاني، وكذلك كان للمبني للمجهول أهمية في التعبير عما في نفس المتكلم، وهو ظاهرة لغوية خاصة باللغات السامية، لكنه اختفى، ولم يبق له أثر إلا في العربية، ودرسه لغويو العربية دون أن يتفقوا على مصطلحه، واختلفوا في كونه بناء أصيلا أو مغيرا عن المبني للمعلوم، وقد ميل إلى أنه مغير عن المبني للفاعل، وأن حذف فاعله كان لأسباب، منها: الجهل به، والعلم به، وتنزيهه، وعدم الحاجة إليه، وإذا حذفوا الفعل ترتب على الفعل تغييرات، فالماضي السالم يضم أوله ويكسر ما قبل آخره، ومن العرب من يسكن عينه تخفيفا، وفي مضعف الثلاثي لغات ثلاث، ضم فائه، والإشمام، وكسرها، وكذلك الأجوف، مع الاختلاف في أعلى اللغات وفي أدناها، والمثال كالصحيح مع جواز قلب الواو همزة، والمزيد والرباعي ومزيده كالثلاثي غير أنهم يضمون أول متحرك، وينقلون كسر العين إلى الفاء إذا كانت العين ألفا، ثم يقلبونها ياء، نحو: استعاد: استعيد، وإذا كان مزيدا بتاء ضموا التاء والفاء، والمضارع يضم أول متحرك فيه، ويفتح ما قبل الآخر، مع نقل الفتحة إلى الفاء إذا كان أجوفا. This is a linguistic research that deals with the phenomenon of the passive building in the Arabic language, and it was made into an introduction, two chapters, and a conclusion. As for the first topic, it dealt with general issues of the passive building, one of which is the importance of the verb in the language, from which verbs and nouns are derived so that the language expands to express meanings, and so was The passive voice has importance in expressing what is in the same speaker, and it is a linguistic phenomenon specific to Semitic languages, but it disappeared, leaving no trace except in Arabic, and Arabic linguists studied it without agreeing on its term, and they differed in its being an original building or a change from the building for the known, and it tended to that it is a change from the predicate of the accusative, and that the deletion of its subject was for reasons, including: ignorance of it, knowledge of it, disdain for it, and lack of need for it, And if they omit the verb, the verb results in changes. The past tense includes its beginning and breaks what is before its end, and among the Arabs there are those who inhabit the same with ease, and in the three-linguistic double, he combined the fa’, the sham, and breaking them, as well as the hollow, with the difference in the highest and lowest languages, and the example is as correct with The permissibility of reversing the waw hamza, the more, the quadrilateral and its more like the triple, except that they include the first movable, and they transfer the fraction of the eye to the fa if the eye is a thousand, then they turn it ya, towards: regained: restored, and if it is more baa, they include the ta and fa, and the present includes the first of your store in it and opens what Before the other, with the transfer of the hole to the F if it is hollow."
Keywords: اللغات السامية -- اللغة العربية -- النحو العربي -- الجملة الفعلية -- الفعل للمجهول